Government Coordination in Data Synchronization of the Family Harapan Program (PKH) In Pujud District, Rokan Hilir Regency - Putri Azzahara; Muhammad Adnan; Teguh Yuwono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Family Hope Program aims to develop social protection for the poor in Indonesia. The PKH program helps reduce the burden of responsibility and change the lifestyle of poor families by providing cash assistance to meet their needs for Very Poor Households (RTSM) by providing conditional cash transfers as recipients of assistance provided in the health and education fields to non-healthy families who can meet their needs. daily. Similar to Rokan Hilir Regency, errors occurred in Pujud Regency due to the district government's lack of prudence in handling the problem, so that many recipients were not properly targeted. The purpose of this research is to find out how the government coordinates poverty data in the Central Statistics Agency of Rokan Hilir Regency and what are the obstacles to government coordination related to the PKH program in Pujud Regency. The theory used is Inu Kenchana Shafee's Government Coordination Theory on Coordination Elements: Regulation, Synchronization, Cooperation and the Common Good. The research methodology used is descriptive and qualitative to provide a clear picture of the management that occurs in the context of coordinating the Family Hope Program. Data collection techniques were carried out using interviews and documentation. The result of this study is that state coordination in synchronizing PKH data is still not optimal. This can be seen from the coordination between the village government and the district government where communication is still not running. In addition, the government's obstacle in coordinating PKH is the lack of human resources and government coordination.